Niobe — Hybris. Eccessi della funzione materna (Materiali di Estetica. Terza serie, 2024)
The notion of limit, intrinsic to the representational universe of the Greeks, coexists with its violation, with ὕβρις which always implies a destructive attitude, both of the individual and of entire human groups. The ὕβρις of the Theban queen Niobe, daughter of Tantalus, is closely connected to her maternal function, to her pride in her powerful fertility - twelve or fourteen children - from which arises the impulse to go beyond human nature to the point of impious denigration of a goddess, Latona, mother of "only" two children: Apollo and Artemis. Tremendous is the divine vengeance that befalls Niobe's offspring to the point of extinction of her lineage. The irreparable mourning makes her a rigid and mute figure, like the stone into which she is transformed: Lydia's Weeping Rock. Through the reading of the fragmentary texts of Aeschylus and Sophocles and the comparison with other literary and figurative testimonies from different eras we understand how deep the mythical story of Niobe has affected the artistic imagination of all time. Niobe's instantaneous petrification is thus reversed in her artistic survival. The durability of the rock which, eroded by rain / tears, continues to transform, is perhaps the extreme counterbalance that mortals oppose to divine revenge. The only authentic way out of the uncertainty of time and the premonition of finitude as well as the inexorability of the limit in the artist's creation.
Keywords: Niobe; myth and metamorphosis; hybris of hypermaternal role; work of the Negative; Alberto Savinio